Identification of RNA markers associated with Parkinson's disease using multiplex gene expression analysis - Natalia S. Ardashirova; Natalia Yu. Abramycheva; Ekaterina Yu. Fedotova; Vladimir S. Sukhorukov; Anastasiya S. Voronkova; Natalia M. Mudzhiri; Sergey N. Illarioshkin (Анналы клинической и экспериментальной неврологии, 2022)
Introduction. Parkinson's disease (PD) is a neurodegenerative disorder, and the development of biomarkers is essential due to complicated PD diagnosis and progression assessment.